Toxicity of Per- and Polyfluoroalkyl Substances and Their Substitutes to Terrestrial and Aquatic Invertebrates—A Review - Jiaxin Zhang; Hassan Naveed; Keping Chen; Liang Chen (Toxics)
Per- and polyfluoroalkyl substances (PFASs) have been widely used in daily life but they cause certain impacts on the environment due to their unique carbon–fluorine chemical bonds that are difficult to degrade in the environment. Toxicological studies on PFASs and their alternatives have mainly focused on vertebrates, while terrestrial and aquatic invertebrates have been studied to a lesser extent. As invertebrates at the bottom of the food chain play a crucial role in the whole ecological chain, it is necessary to investigate the toxicity of PFASs to invertebrates. In this paper, the progress of toxicological studies on PFASs and their alternatives in terrestrial and aquatic invertebrates is reviewed, and the accumulation of PFASs, their toxicity in invertebrates, as well as the neurotoxicity and toxicity to reproduction and development are summarized. This provides a reference to in-depth studies on the comprehensive assessment of the toxicity of PFASs and their alternatives, promotes further research on PFASs in invertebrates, and provides valuable recommendations for the use and regulation of alternatives to PFASs.